2017
DOI: 10.1038/s41598-017-03938-9
|View full text |Cite
|
Sign up to set email alerts
|

Residential radon exposure and brain cancer: an ecological study in a radon prone area (Galicia, Spain)

Abstract: We aimed to know if radon concentration is associated with municipal mortality due to brain cancer in Galicia, Spain. We designed an ecological study taking as study unit Galician municipalities. To be included, municipalities had to have at least three radon measurements. We correlated radon concentrations with municipal mortality due to these malignant tumors during the period 1999–2008. We calculated the relative risk of dying of brain cancers for each municipality and correlated this value with municipal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Our finding that women had higher 210 Po levels among different tissues than men are consistent with previous research. Ruano-Ravina et al examined the association between residential radon levels and brain cancer mortality in Galicia, Spain, and showed that the risks were higher among women 29 . The authors attributed this to the fact that women spend more time in residential environments as compared to men 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that women had higher 210 Po levels among different tissues than men are consistent with previous research. Ruano-Ravina et al examined the association between residential radon levels and brain cancer mortality in Galicia, Spain, and showed that the risks were higher among women 29 . The authors attributed this to the fact that women spend more time in residential environments as compared to men 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Ruano-Ravina et al examined the association between residential radon levels and brain cancer mortality in Galicia, Spain, and showed that the risks were higher among women 29 . The authors attributed this to the fact that women spend more time in residential environments as compared to men 29 . Furthermore, the reduced capacity of pulmonary clearance observed in women and smoking individuals might explain our lung tissue findings.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for a correlation between chronic exposure to radon and mortality due to malignant brain tumors. Nevertheless, this study had a non-robust epidemiological design to confirm this finding [ 81 ]. Additionally, in studies on the occurrence of the radon decay products 210 Po and 210 Bi in the brain of persons suffering from Alzheimer’s or Parkinson’s disease, an inhomogeneous distribution of these nuclides was found, but these findings are not sufficient to draw conclusions concerning correlative underlying mechanisms [ 82 , 83 ].…”
Section: Cancer Riskmentioning
confidence: 99%
“…Some epidemiological studies have suggested a positive correlation between environmental radon exposure and prostate cancer [50]. A study in Galicia (Spain) showed a correlation between brain cancer mortality and indoor radon exposure [51].…”
Section: Health Effect Of Radonmentioning
confidence: 99%